PRAKTIK YOGA SEBAGAI SOSIAL RELIGIUS MEMBENTUK PERILAKU SUSILA - Juniartha, Made G. (JURNAL YOGA DAN KESEHATAN, 2020)
Human life getting caught up in things that are worldly. Humans tend to very easily tied to wealth, power, and ambition is so great without control. So sometimes there are gaps and deficiencies perceived in him. Only wealth, power and ambition deemed able to meet the emotional, physical and human egositas, while the most important thing that should be prioritized rarely get attention, it is the soul and spiritual needs of people. Man must remember him as a religious element in the control function as individuals and social beings of any action taken.The practice of yoga which include aspects of moral, physical, mental and spiritual levels influence human behavior. Especially in the era of globalization, in addition to contributing to the positive as well negative impact if the absence of self-control. Yoga as a Hindu religion became a social phenomenon as a social category as the control of the religious self. Yoga is a religious practice that is understood as an experience in a state or in a state transcends aware of unconscious self, into the presence of God. By being able to balance the body and mind through yoga practices, yoga practitioners practicing slowly with continuity Tri K?ya Parisudha teaching concept (think, say and do what is good and pure). So Increase faith and self introspection for yoga practitioners.